Engaging Secondary School Students In Word Mapping Strategy In Learning General Vocabulary of Descriptive Text: A Classroom Action Research - Ayu, Ayu; Ridwan, Iwan; Yanto, Elih Sutisna (Journal of Educational Sciences, 2025)
The aim of the study is to find whether Word Mapping Strategy can engage Secondary school students in learning general vocabulary of descriptive text. In order to achieve the research objectives, a classroom action research was used as a research design in this study. The participants of this study were 23 students of class VIII in one of Islamic secondary schools. The results of the study showed that word mapping strategy is effective to engage students in learning vocabulary. Most of students respond positively to the use of this strategy. The students feel satisfied with this strategy. They said that this strategy give them many benefits such as increasing students’ vocabulary, give the clearer meaning and make students feel motivated in the learning process. However, even though word mapping has many positive impacts, this strategy also makes students feel challenged, especially when students are asked to make word map charts in their notebooks. Therefore, this research finding can be studied more deeply for the future research to resolve the emerged problem. From the results of the research, it can be concluded that this strategy is highly recommended to be applied for the teacher in teaching vocabulary.